Economic Ties between China and Nigeria: A Study of President Muhammadu Buhari's Administration from 2015 - 2022 - Benjamin E. Agah; Francis. A Ikenga (PERSPEKTIF, 2023)
The study focused on China-Nigeria economic ties as well as long-term democratic stability in Nigeria. The study took a traditional data collection approach, which included a careful and methodical investigation of secondary data. The findings show that Nigeria suffers as a result of China-Nigeria relations. The study also revealed that China's economic goals are driven by strong political, ideological, and economic ambitions rather than altruism. Although China has been extremely helpful in providing loans for Nigeria's critical infrastructure development, there is a risk of debt trapping due to Nigeria's political class' proclivity to mismanage collected funds and ensure that all debts are paid back. The research ended with the following recommendations: Nigerian officials should make the most of Chinese investment in infrastructure development in order to encourage sustainable growth in the country. In addition to creating an open, secure, and politically stable macroeconomic environment, the Nigerian government must craft comprehensive and alluring investment policies. Access to carefully crafted repayment plans for the loans obtained from China to fund infrastructure projects must be available to Nigerians. By doing this, the governments will be held accountable and responsible. To avoid damaging future generations, measures should be made to ensure accountability in the utilization of any loans obtained. All loans should be appropriately allocated to initiatives that enhance the welfare of the populace.